Current Sensing Techniques and Biasing Methods for Smart Power Drivers - Easwaran, Sri Navaneethakrishnan (Springer International Publishing, 2018)
This book provides a detailed description of fault tolerant design techniques for smart power drivers and their application in the design of automotive airbag ICs to ensure correct deployment. The book begins with an introduction to the nature of electrical loads in the car, then moves on to describe various current sensing circuits, featuring thermal simulations. It shows how simple design techniques can be applied to ensure appropriate functionality of the IC under any power up condition. It concludes by introducing diagnostic circuits and measurement results. This book is a useful reference for automotive IC designers and provides specifications and design guidelines not found in the current literature. Provides a comprehensive reference for airbag squib drive IC designers Demonstrates how simple design techniques can be applied to ensure appropriate functionality Details high power IC design for automotive airbags.